Nanotechnologie ve výuce přírodních věd - Vaníčková, Markéta; Soukupová, Jana; Kvítek, Libor (Chemické listy, 2010)
Nanomaterials are now produced in large quantities due to their useful properties different from other materials. Possible toxicity of nanomaterials is currently addressed and discussed. Using a modified Tollens process, an aqueous dispersion of Ag nanoparticles was prepared, on which their unique properties and changes of material characteristics when approaching nano dimensions can be demonstrated. Also, experiments regarding toxicity of nanoparticles were proposed. Toxicity of the nanoparticles was tested on Paramecium caudatum. Following the instruction, the students discover that the prepared Ag nanoparticles are much less toxic than ionic Ag. The proposed experiments bring interdisciplinary chemical, physical, and biological findings and knowledge.
Keywords: přírodní vědy; financování organizované; Colloids; mikrochemie; testy toxicity; antiinfekční látky; Nanoparticles; nanotechnologie; Anti-Infective Agents; stříbro; Paramecium caudatum; Silver; koloidy; Nanotechnology; Natural Science Disciplines; Financing, Organized; Education; Humans; výchova a vzdělávání; chemické techniky analytické; nanočástice; Chemistry Techniques, Analytical; Microchemistry; Toxicity Tests; lidé